2023
DOI: 10.1039/d2mh01293f
|View full text |Cite
|
Sign up to set email alerts
|

Controlling selectivity for dechlorination of poly(vinyl chloride) with (xantphos)RhCl

Abstract: Reactions of poly(vinyl chloride) (PVC) with a rhodium catalyst and H-donors reveal how reaction conditions can impact the selectivity for chloride removal, with sodium formate showing the highest selectivity for hydrodechlorination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…65 Another example, introduced by Fieser and coworkers, uses (xantphos) Rh catalysts and hydrogen donors (i.e., sodium hydride, sodium formate, triethylsilane) to enable selective hydrodechlorination to polyethylene-like materials with 63% substitution efficiency. 66 Optimizing dechlorination efficiency and selectivity simultaneously, while challenging, could be instrumental in yielding versatile recycling approaches. Previous studies have shown that choosing appropriate reaction conditions, including nucleophile identity, temperature, concentration, and solvent polarity (summarized in the Structure and reactivity section), could lead to reactions with higher substitution efficiency.…”
Section: Heterolytic Dechlorinationmentioning
confidence: 99%
See 2 more Smart Citations
“…65 Another example, introduced by Fieser and coworkers, uses (xantphos) Rh catalysts and hydrogen donors (i.e., sodium hydride, sodium formate, triethylsilane) to enable selective hydrodechlorination to polyethylene-like materials with 63% substitution efficiency. 66 Optimizing dechlorination efficiency and selectivity simultaneously, while challenging, could be instrumental in yielding versatile recycling approaches. Previous studies have shown that choosing appropriate reaction conditions, including nucleophile identity, temperature, concentration, and solvent polarity (summarized in the Structure and reactivity section), could lead to reactions with higher substitution efficiency.…”
Section: Heterolytic Dechlorinationmentioning
confidence: 99%
“…The previously described study by Fieser and coworkers (Scheme 6B), which leverages hydride donors, offers a pathway for simultaneously recycling the carbon content of the polymer and generating potentially valuable Cl-containing byproducts (e.g., chlorotriethylsilane when Et 3 SiH is used). 66 However, the required catalysts and hydrogen sources are expensive, potentially challenging economic viability. Additionally, a more selective substitution would help limit dehydrochlorination side reactions, adding value to the resulting polyethylene-like materials.…”
Section: The Future Of Chemical Pvc Recyclingmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The third method is to dechlorinate PVC selectively through reduction or hydrodechlorination to form PE-like materials using catalytic methods or stoichiometric reagents such as Bu 3 SnH. 18–20 However, these reports either don't achieve full dechlorination, or if full dechlorination is achieved the polymer product does not have the necessary purity and thermal properties to enter the PE mechanical recycling stream (Fig. 1C).…”
Section: Introductionmentioning
confidence: 99%
“…10 Complementarily, a (Xantphos)RhCl reduction catalyst was applied for controlled hydrodechlorination of PVC using a range of reducing agents, including trialkylsilanes and NaH. 10,11 However, the selectivity for hydrodechlorination versus the competing dehydrochlorination is not always easily controlled. Although full dechlorination is possible for virgin PVC, several limitations persist, such as the use of costly silanes or organic H-sources as reagents with poor atom economy, the use of aromatic solvents, and the necessity of specialized ligands to enhance the activity of Ru.…”
Section: Introductionmentioning
confidence: 99%